Implementasi Model Pembelajaran Trait Treatment Interaction (TTI) Menggunakan Multimedia Swishmax 4.0 - aswirna, prima (Universitas Islam Negeri Imam Bonjol Padang, 2018)
his research is motivated by the low learning outcomes of students, namely the same treatment given by educators to students in the classroom, whereas each individual has different characteristics or different abilities. Educators should adjust the learning model that is appropriate to the ability of each student, because students are smart, medium, and low. Besides that other causes include conventional learning,Â educators only provide formulas without using interactive, interesting, fun and not boring media for learning, then giving training to students. This study aims to find out that the learning outcomes of science students by applying the Trait Treatment Interaction (TTI) learning model is better than conventional learning in class VIII MTsN Durian Tarung padang. This type of research is Quasy Experiment with Randomized Control Group Only Design design. The sample was selected using Cluster Random Sampling technique and obtained class VIII5 as an experimental class and class VIII6 as a control class. Analysis of test data using t-test statistical techniques with a significant level, obtained t count> t table thitung. So, it can be concluded that the application of Multimedia Swishmax 4.0-assisted TTI model provides better science learning outcomes than conventional learning in the eighth grade MTsN Durian Tarung Padang.